Associative-verbal network as a reflection of markers of the national identity of Sakha people - Evdokimova, Sofya (UNISC, 2022)
Abstract: The paper discusses the national culture Sakha language consciousness presented on the Yakut Associative dictionary, whose methodology was based on a mass associative experiment, resulted in an associative-verbal network, allowing not only a person's verbal memory fragment identification, but also a particular culture carriers of the world systemic image revelation. The author analyses the linguistically represented northern ethnos culture traditional values through the prism of socio-cultural and linguistic processes determined by the globalized context. An attempt was made to identify the meanings that an ethnic group representatives put into certain traditional worldview key elements, national identity daily markers of the Sakha consciousness to understand their significant role in certain nation’s traditional national identity and culture formation and preservation. Keywords: language consciousness; national identity and culture; associative-verbal network; worldview; lexicon. Resumo: O artigo discute a consciência linguística da cultura nacional Sakha apresentada no dicionário Associativo Yakut, cuja metodologia foi baseada em um experimento associativo de massa, resultou em uma rede associativo-verbal, permitindo não apenas a identificação de fragmentos de memória verbal de uma pessoa, mas também portadores da cultura da revelação da imagem sistêmica mundial. O autor analisa os valores tradicionais da cultura etno-norte, representados linguisticamente pelo prisma dos processos socioculturais e linguísticos determinados pelo contexto globalizado. Procurou-se identificar os significados que os representantes de um grupo étnico colocam em certos elementos-chave da visão de mundo tradicional, marcadores diários da identidade nacional da consciência Sakha para entender seu papel significativo na formação e preservação da identidade nacional tradicional de determinada nação e da cultura. Palavras-chave: consciência da linguagem; identidade e cultura nacional; rede associativo-verbal; visão de mundo; léxico.